'Rail and Nail' bifocal management of atrophic femoral nonunion. (May 2018) - Davda, K.; Heidari, N.; Calder, P.; Goodier, D.
Abstract : Aims: The management of a significant bony defect following excision of a diaphyseal atrophic femoral nonunion remains a challenge. We present the outcomes using a combined technique of acute femoral shortening, stabilized with a long retrograde intramedullary nail, accompanied by bifocal osteotomy compression and distraction osteogenesis with a temporary monolateral fixator. Patients and Methods: Eight men and two women underwent the 'rail and nail' technique between 2008 and 2016. Proximal locking of the nail and removal of the external fixator was undertaken once the length of the femur had been restored and prior to full consolidation of the regenerate. Results: The mean lengthening was 7 cm (3 to 11). The external fixator was removed at a mean of 127 days (57 to 220). The mean bone healing index was 28 days/cm and the mean external fixation index was 20 days/cm (11 to 18). There were no superficial or deep infections. Conclusion: This small retrospective study shows encouraging results for a combined technique, enabling compression of the femoral osteotomy, alignment, and controlled lengthening. Removal of the fixator and proximal locking of the nail reduces the risk of complications and stabilizes the femur with the maximum working length of the nail. Cite this article: Bone Joint J 2018;100-B:634–9.